Systematic review of adherence to direct oral anticoagulants in patients with atrial fibrilation in clinical practice - Kubas, Mohammed Abdullah; Zin, Che Suraya; Shabaruddin, Fatiha Hana (2018)
Direct oral anticoagulants (DOACs), such as dabigatran and rivaroxaban, have in the past decade replaced vitamin k antagonists (VKAs), such as warfarin, as standard treatment for thrombosis prophylaxis and stroke prevention in patients with atrial fibrillation (AF). Adherence to DOACs is crucial to optimise clinical outcomes in patients with AF. The aim of this review is to systematically evaluate published evidence describing adherence to DOACs in patients with AF in real world clinical practice. A systematic search combining terms for direct oral anticoagulants, atrial fibrilation and relevant adherence measurement tools was conducted in PubMed in March 2018 to identify related English language publications. All observational cohort studies that assessed adherence of DOACs in patients with AF by using healthcare institution databases, including pharmacy records, medical claims datasets, and other relevant data were reviewed for inclusion. Data describing study characteristics and adherence profile were extracted and summarised using qualitative methods. The PubMed search identified 278 citations. After screening the titles and abstracts, full articles were obtained for 36 articles and of these, 22 articles were included. These 22 studies involved around 300,000 AF patients, described the adherence of DOACs in clinical practice in the United States, Europe, and Turkey and were published between 2013 to 2018. Proportion of days covered (PDC) was the most commonly used tool for adherence measurement followed by medicine possession ratio (MPR). Adherence to DOACs was found to be good in most studies, defined as PDC ≥80% and MPR ≥80%. While these published evidence indicated that adherence to DOACs in real world clinical practice is generally good, clinical outcomes can be optimised by identifying AF patients with sub-optimal adherence and developing interventions to improve adherence in these patients within clinical practice.